The Mirror of Intelligence and the Controversy on Christ’s Unction in the Ethiopian Church - Casella, Giulia (Aethiopica, 2024)
The present article examines the theological treatise The Mirror of Intelligence within the context of the controversy about Christ’s unction in the Ethiopian Church during the seventeenth century. The introductory section offers an overview of the early phase of the debate, presenting the diverse positions involved and tracing the evolution of the theological dispute. The subsequent two sections delve into the use of rhetorical devices in The Mirror of Intelligence and other contemporary theological works. Through this analysis, the article explores the intersection of creativity and religious reflection in literary production, shedding light on the pivotal role of figurative language as a medium of theological discourse.